2015
DOI: 10.1080/15476286.2015.1017212
|View full text |Cite
|
Sign up to set email alerts
|

No effect of an elevated miR-30b level in mouse milk on its level in pup tissues

Abstract: (2015) No effect of an elevated miR-30b level in mouse milk on its level in pup tissues, RNA Biology, 12:1, 26-29, DOI: 10.1080/15476286.2015 Keywords: diet, horizontal genetic transfer, microRNA, milk, transgenic mouseRecent reports have shown that ingested microRNAs may be transferred to blood, accumulate in tissues and exert canonical regulation on endogenous transcripts. In spite of several attempts to replicate these findings, they have not been confirmed and several questions remain. By using a transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 25 publications
(50 reference statements)
1
45
0
1
Order By: Relevance
“…99,100 Transgenic mouse studies found no uptake of specific milk microRNAs. 101,102 Finally, positive results from a milk intake study involving humans 103 could not be validated. 104 Exciting and new concepts in the microRNA oeuvre must be supported by rigorous data.…”
Section: Case Studies To Identify Rigor and Reproducibility Challengementioning
confidence: 99%
“…99,100 Transgenic mouse studies found no uptake of specific milk microRNAs. 101,102 Finally, positive results from a milk intake study involving humans 103 could not be validated. 104 Exciting and new concepts in the microRNA oeuvre must be supported by rigorous data.…”
Section: Case Studies To Identify Rigor and Reproducibility Challengementioning
confidence: 99%
“…It has been suggested that miRNAs can be transferred from breast milk to the bloodstream (Munch et al 2013;Baier et al 2014;Izumi et al 2015), although these results have also been contested (Laubier et al 2015;Title et al 2015).…”
Section: Controlled Feeding In Piglets Does Not Support Transfer Of Mmentioning
confidence: 99%
“…42,46 Significantly increased concentration of miR-30b was observed in the milk of transgenic mice, but no alteration in its concentration in milk-fed pup tissues was found. 47 A major weakness of this study is that the authors have not evaluated miR-30b concentration in exosomes, and overexpressed miR-30b might interfere with the formation of exosomes due to defects in mammary epithelium of transgenic mice. 42 In the other 2 models, miR-375 and miR-200c/141 knockout mice fed by wild-type wet nurse mice were explored.…”
Section: Dietary Milk-derived Mirnasmentioning
confidence: 99%